2007
DOI: 10.1121/1.2722047
|View full text |Cite
|
Sign up to set email alerts
|

Focused intracochlear electric stimulation with phased array channels

Abstract: A method is described for producing focused intracochlear electric stimulation using an array of N electrodes. For each electrode site, N weights are computed that define the ratios of positive and negative electrode currents required to produce cancellation of the voltage within scala tympani at all of the N-1 other sites. Multiple sites can be stimulated simultaneously by superposition of their respective current vectors. The method allows N independent stimulus waveforms to be delivered to each of the N ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…Therefore, efforts to reduce current spread have been proposed that could lead to the reduction of subthreshold effects and the targeting of smaller subpopulations of SGNs per channel. Some promising methods are being developed for more accurately steering current towards the intended SGNs, such as using bipolar, tripolar, or even multipolar electrode configurations (van den Honert and Kelsall 2007).…”
Section: Spatial Effects Of CI Stimulation Related To Temporal Interamentioning
confidence: 99%
“…Therefore, efforts to reduce current spread have been proposed that could lead to the reduction of subthreshold effects and the targeting of smaller subpopulations of SGNs per channel. Some promising methods are being developed for more accurately steering current towards the intended SGNs, such as using bipolar, tripolar, or even multipolar electrode configurations (van den Honert and Kelsall 2007).…”
Section: Spatial Effects Of CI Stimulation Related To Temporal Interamentioning
confidence: 99%
“…They agreed to use the research device for 18 months and to participate in research during this time. While not participating in experiments, the participants connected their research implant to a standard sound processor programmed with the ACE strategy (Vandali et al 2000) using a custom-designed dongle (van den Honert and Kelsall 2007). After the research period, participants were explanted and reimplanted with a standard commercial cochlear implant.…”
Section: Participants and Equipmentmentioning
confidence: 99%
“…Van den Honert and Kelsall (2007) have demonstrated that if the impedance matrix between all pairs of electrodes can be measured, it is possible to create a potential field localized around one targeted electrode. By selecting simultaneous current levels and phases on each electrode appropriately, the sum of all potentials can result in a gradient confined to a very specific place in the cochlea (schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations